Pre-Irradiation Comparison of W-Based Alloys for the PHENIX Campaign: Microstructure, Composition, and Mechanical Properties. (18th August 2019) - Lang, Eric; Reid, Nathan; Garrison, Lauren; Parish, Chad; Allain, J. P.
Abstract: Tungsten is the material of choice as the plasma-facing material in future plasma-burning fusion reactors. During operation, plasma-facing materials will be simultaneously exposed to 14-MeV neutrons, low-energy D/He particles, and high heat loads. Neutron irradiation of tungsten results in bulk material damage, including knock-on damage causing loops and voids, and transmutation reactions leading to the transmutation of tungsten to rhenium and osmium. Under irradiation to high dose, Re and Os atoms can amalgamate into precipitates that drastically alter the material properties, noticeably increasing the hardness. However, the early-stage development of Re and Os precipitates under a fast neutron spectrum has not been investigated. In this work, the microstructure and hardening behavior of W-Re alloys containing 0 to 2.2 wt% Re, TiC-doped W, and powder-injection-molded W are investigated prior to neutron irradiation at 500ºC and 800ºC to 0.1 displacement per atom in the High Flux Isotope Reactor (HFIR) to establish a baseline understanding of the starting microstructures. Transmission electron microscopy analysis indicates a dislocation-heavy microstructure, and scanning transmission electron microscopy–energy dispersive spectroscopy shows no spatial segregation of Re and W. Similarly, surface compositional studies performed with electron backscatter diffraction and X-ray photoelectron spectroscopy showed no presence of Re, indicating the Re did not segregate or form new phases during fabrication. The alloys in their as-fabricated state showed no Re segregation or second-phase development, with no significant differences between their microstructures and Vickers hardness values.